Ileostomy Prolapse in Children with Intestinal Dysmotility. (18th September 2017) - Sparks, Eric A.; Velazco, Cristine S.; Fullerton, Brenna S.; Fisher, Jeremy G.; Khan, Faraz A.; Hall, Amber M.; Jaksic, Tom; Rodriguez, Leonel; Modi, Biren P.
Abstract : Background . A relationship between intestinal motility and ileostomy prolapse has been suggested but not demonstrated objectively. Aims . This study evaluated the association between ileostomy prolapse and intestinal dysmotility in children. Methods . IRB-approved retrospective review of 163 patients with ileostomies (1998–2014) at a single institution. Patients were categorized as having clinical dysmotility as a primary diagnosis (n = 33 ), clinically suspected dysmotility based on underlying diagnosis (n = 60 ), or intestinal dysmotility unlikely (n = 70 ) at the time of ileostomy present. Intestinal manometry was categorized as normal (n = 13 ) or abnormal (n = 10 ). Primary outcome was pathologic stoma prolapse. Multivariate analysis using a logistic regression model and log-rank test to compare stoma prolapse rates over time between motility groups were used. Results . Clinical diagnosis of dysmotility (p ≤ 0.001 ) and manometric findings of dysmotility (p = 0.024 ) were independently associated with stoma prolapse. Clinical dysmotility correlated with manometric findings (κ = 0.53 ). Prolapse occurred in 42% of patients with dysmotility, 34% of patients with suspected dysmotility, and 24% of patients with normal motility. One-year prolapse-free stoma "survival" was 45% for dysmotility, 72% for suspected dysmotility, and 85% for intestinal dysmotility unlikely groups (p = 0.006 ). Conclusions . Children with intestinal dysmotility are at great risk for stoma prolapse. Intestinal manometry could help identify these patients preoperatively.